RETRACTED: Oroxylin a Inhibits the Protection of Bone Marrow Microenvironment on CML Cells Through CXCL12/CXCR4/P-gp Signaling Pathway - Cao, Hanbo; Li, Wenjun; Zhou, Yizhou; Tan, Renxiang; Yang, Yue; Zhou, You; Guo, Qinglong; Zhao, Li (Frontiers in Oncology, 2019)
Imatinib (IM) resistance significantly affects the survival rate of patients with chronic myeloid leukemia (CML). Previous studies have shown that the protective effect of the bone marrow stroma cells (BMSCs) on CML cells is achieved by secreting CXCL12. The aim of this study was to investigate whether oroxylin A could reverse the protective effect of BMSCs on CML and illuminate the underlying mechanisms. The results showed that CXCL12 could enhance the resistance of K562 and KU812 cells to IM by increasing the expression of CXCR4, promoting translocation of β-catenin into nucleus and subsequently increasing the expression of P-gp in K562 cells. And IM resistance was partially reversed by CXCR4 siRNA transfection. Moreover, the reverse effect of oroxylin A was demonstrated by inhibiting β-catenin/P-gp pathway via decreasing the expression of CXCR4 in vitro. The in vivo study also showed that oroxylin A decreased the expression of P-gp and β-catenin proteins in mice bone marrow with low systemic toxicity, and the mechanism was consistent with the in vitro study. In conclusion, all these results showed that oroxylin A improved the sensitivity of K562 and KU812 cells to IM in BM microenvironment decreasing the expression of CXCR4 and inhibiting β-catenin/P-gp pathway.